Studi Kualitas Aspal Buton PT Wijaya Karya Bitumen, Kabupaten Buton, Provinsi Sulawesi Tenggara: Buton Asphalt Quality Study of PT Wijaya Karya Bitumen, Buton Regency, Southeast Sulawesi Province - Arham; Bakri, Hasbi; Bakri, Suriyanto (Journal of Engineering Science and Technology Applications, 2024)
Utilization of Buton asphalt is not too maximal, it is because the quality of Buton asphalt is considered less favorable than asphalt oil. The aim of this study was to determine the percentage content of bitumen and water content at the mine site and Lawele Kabungka. Methodology The study was entirely based on laboratory data required data¬-related data quality is seen from the Buton asphalt bitumen content and moisture content of the samples taken in the field. In addition, data were also taken from the test results Research and Development Center (PUSLITBANG) Department of Public Works (PU) in the form of data ductility, penetration, flash point, softening point, lose weight, solubility in CCl4 on the content of the asphalt in two locations: Lawele and Kabungka , Based on the results of research conducted in the laboratory PT. Wijaya Karya Bitumen bitumen shows that the average levels for Lawele Buton Asphalt Bulk 28.79% and Lawele (LGA) 29.53%, while in Kabungka with an average of Buton Asphalt Bulk 25.52% and Kabungka (BGA) 26 , 83%. Both locations meet ISO standards, both asphalt in bulk form or in the form of LGA and BGA is 25%. Buton asphalt water content is quite high at the location Lawele (Buton Asphalt Bulk of 13.2%, LGA of 7.93%) and Kabungka (Buton Asphalt Bulk 11.03% BGA 8.9%). The water content of the two locations do not meet the National Standards of Indonesia (SNI) either in bulk form or in the form of BGA and LGA is constant below 2%.